Factors controlling the export of nitrogen from agricultural land in a large central European catchment during 1900-2010 - Kopáček, Jiří; Hejzlar, Josef; Posch, Maximilian (Environmental science & technology, 2013)
Using an empirical model, we quantified the nitrogen (N) export from agricultural land in a large central European catchment (upper Vltava river, Czech Republic, about 13,000 km(2)) over the 1959-2010 period. The catchment witnessed a rapid socio-economic shift from a planned to a market economy in the 1990s, resulting in an abrupt (~50%) reduction in N fertilization rates at otherwise relatively stable land-use practices. This large-scale "experiment" enabled disentangling and quantification of individual effects of N fertilization and drainage on N leaching. The model is based on a two-step regression between annual N export and three independent variables: (i) annual average discharge in the first step and (ii) net anthropogenic nitrogen inputs (NANI) and proportion of drained agricultural land in the second step. Results show that N export was more related to mineralization of soil organic N pools due to drainage and tillage than to external N sources (NANI). The model, together with other reconstructed N sources in the catchment (leaching from forests, waste waters, and atmospheric deposition) and extrapolated back to 1900, explained 77% of the observed variability in N concentrations in the Vltava river during the 1900-2010 period.
Keywords: Europe; teoretické modely; Evropa; Models, Theoretical; zemědělství; Nitrogen; dusík; Environmental Monitoring; monitorování životního prostředí; Agriculture